2018
DOI: 10.1101/460071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Guiding the Refinement of Biochemical Knowledgebases with Ensembles of Metabolic Networks and Machine Learning

Abstract: Mechanistic models are becoming common in biology and medicine. These models are often more generalizable than datadriven models because they explicitly represent biological knowledge, enabling simulation of scenarios that were not used to construct the model. While this generalizability has advantages, it also creates a dilemma: how should model curation efforts be focused to improve model performance? Here, we develop a machine learningguided solution to this problem for genomescale metabolic models. We gene… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Tests evaluating network topology can be used to evaluate the more subjective features of the model, by using connectedness as a proxy for inferring the scope of manual curation or the quality of a reconstruction. However, this requires such topological measures (and/or machine learning; Medlock & Papin, ) to be combined with biological knowledge of the system. Condition‐specific tests (often referred to as “metabolic tasks” in the COBRA field) are developed to evaluate the biological meaning of the network and attempt to represent specific biochemical experiments.…”
Section: Standardization In Metabolic Modeling: a Case Studymentioning
confidence: 99%
“…Tests evaluating network topology can be used to evaluate the more subjective features of the model, by using connectedness as a proxy for inferring the scope of manual curation or the quality of a reconstruction. However, this requires such topological measures (and/or machine learning; Medlock & Papin, ) to be combined with biological knowledge of the system. Condition‐specific tests (often referred to as “metabolic tasks” in the COBRA field) are developed to evaluate the biological meaning of the network and attempt to represent specific biochemical experiments.…”
Section: Standardization In Metabolic Modeling: a Case Studymentioning
confidence: 99%
“…from the same omics data, and predictions could be based on agreement among models in the ensemble (Biggs and Papin, 2017). Ensemble modeling could also help improve the models themselves by applying machine learning to their contents and predictions (Medlock and Papin, 2020). Indeed, recent studies have demonstrated context-specific ensemble modeling with a single MEM (Rodríguez-Mier et al ., 2021) and combined multiple MEMs to build a single model (Vieira et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…[ 154 ] ML methods such as ensemble methods have shown improvements in the refinements of genome‐scale metabolic reconstructions. [ 155 ] Third, although very accurate, the results of the integrated models are not necessarily appropriate for large‐scale industrial fermentations. This arises from the difference between fermentation conditions in lab‐scale and industrial‐scale bioreactors.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%